Direct Bandgap Transition in Many‐Layer MoS2 by Plasma‐Induced Layer Decoupling. (14th January 2015) - Dhall, Rohan; Neupane, Mahesh R.; Wickramaratne, Darshana; Mecklenburg, Matthew; Li, Zhen; Moore, Cameron; Lake, Roger K.; Cronin, Stephen
<x xml:space="preserve">Abstract</x> We report a robust method for engineering the optoelectronic properties of many‐layer MoS2 using low‐energy oxygen plasma treatment. Gas phase treatment of MoS2 with oxygen radicals generated in an upstream N2–O2 plasma is shown to enhance the photoluminescence (PL) of many‐layer, mechanically exfoliated MoS2 flakes by up to 20 times, without reducing the layer thickness of the material. A blueshift in the PL spectra and narrowing of linewidth are consistent with a transition of MoS2 from indirect to direct bandgap material. Atomic force microscopy and Raman spectra reveal that the flake thickness actually increases as a result of the plasma treatment, indicating an increase in the interlayer separation in MoS2. Ab initio calculations reveal that the increased interlayer separation is sufficient to decouple the electronic states in individual layers, leading to a transition from an indirect to direct gap semiconductor. With optimized plasma treatment parameters, we observed enhanced PL signals for 32 out of 35 many‐layer MoS2 flakes (2–15 layers) tested, indicating that this method is robust and scalable. Monolayer MoS2, while direct bandgap, has a small optical density, which limits its potential use in practical devices. The results presented here provide a material with the direct bandgap of monolayer MoS2, without reducing sample thickness, and hence optical density.